HEALTH RELATED QUALITY OF LIFE IN SCHOOL GOING ADOLESCENTS OF KHYBER PAKHTUN-KHWA PAKISTAN - Siddique, Muhammad; Ayub, Ayaz; Hussain, Hamid (Journal of Ayub Medical College Abbottabad, 2015)
Background: In several countries health related quality of life (HRQoL) scales have been used for adolescents, to assess the impact of disease. Health related quality of life scales are used on a range of different domains: physical, psychological, social and spiritual focusing on personal life including the concept of the World Health Organization definition of health. Methods: Health related quality of life in adolescent going to schools in the cantonment area of Peshawar garrison was assessed in a cross sectional descriptive study. Data was gathered by using a self-administered questionnaire (Kiddo-KINDL-R Questionnaire), previously tested to assess quality of life across six dimensions of health i.e. Physical and emotional well-being, self-esteem, family, social and school. Results: A total of 300 students of average age 13.41±1.34 years, with 145 (48.3%) females. Mean (SD) of total QoL score was 86.98 (12.86). The mean total scores were 86.28±12.34 and 87.64±13.34 for girls and boys, respectively. Conclusion: On the whole quality of life scores of the adolescent are good in the four dimensions. Special attention is needed towards the school environment, as majority of the participants are not satisfied with their schools. Similarly self-esteem scores are also low in the majority. However it is encouraging that most of the participants have scored highest scales in dimensions of family and physical health. Any effort to assess quality of life of the adolescents at the national level will give better view of quality of life of our youth